2014
DOI: 10.1105/tpc.114.130849
|View full text |Cite
|
Sign up to set email alerts
|

BRASSINOSTEROID INSENSITIVE2 Interacts with ABSCISIC ACID INSENSITIVE5 to Mediate the Antagonism of Brassinosteroids to Abscisic Acid during Seed Germination inArabidopsis 

Abstract: Seed germination and postgerminative growth are regulated by a delicate hormonal balance. Abscisic acid (ABA) represses Arabidopsis thaliana seed germination and postgerminative growth, while brassinosteroids (BRs) antagonize ABA-mediated inhibition and promote these processes. However, the molecular mechanism underlying BR-repressed ABA signaling remains largely unknown. Here, we show that the Glycogen Synthase Kinase 3-like kinase BRASSINOSTEROID INSENSITIVE2 (BIN2), a critical repressor of BR signaling, pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
197
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 256 publications
(206 citation statements)
references
References 82 publications
7
197
1
1
Order By: Relevance
“…Finally, it is worthy of attention the fact that heat stress clearly down-regulated gene expression of all ZmBZRs analysed. We speculate that this apparently contrasting result might be explained by considering the antagonistic interaction between BRs and ABA in regulating, for example, seed germination and dormancy during embryo maturation (Hu and Yu 2014). More consistently with our results, it has been demonstrated that high endogenous levels of ABA suppress BR-mediated responses in plant (Divi et al 2010).…”
Section: Discussionsupporting
confidence: 78%
“…Finally, it is worthy of attention the fact that heat stress clearly down-regulated gene expression of all ZmBZRs analysed. We speculate that this apparently contrasting result might be explained by considering the antagonistic interaction between BRs and ABA in regulating, for example, seed germination and dormancy during embryo maturation (Hu and Yu 2014). More consistently with our results, it has been demonstrated that high endogenous levels of ABA suppress BR-mediated responses in plant (Divi et al 2010).…”
Section: Discussionsupporting
confidence: 78%
“…In the network analysis, the hub genes encoding phosphorylation related enzymes in BR (BIN2s) and ABA (PP2Cs) signaling were found closely connected with each other. Coincidently, the antagonism of BR and ABA mediated by BIN2 has been recently evidenced in Arabidopsis seed germination [29]. Taken together, we speculated that BR could promote seed germination partly through the phosphorylation-mediated counteraction to ABA in both dicots and monocots.…”
Section: Discussionmentioning
confidence: 90%
“…Yeast two-hybrid assay was performed as described previously (Hu and Yu, 2014). Primers used for generating various clones for yeast two-hybrid assays are listed in Supplemental Table S1.…”
Section: Yeast Two-hybrid Assaymentioning
confidence: 99%